Persepsi Masyarakat Adiwerna dalam Perkembangan Lembaga Keuangan Syariah terhadap Minat Menggunakan Bank Syariah - Sylviana Salsabila Sylvi; Naela Himatutsaroya; Sekar Ayu Lestari (Institut Agama Islam Negeri Parepare, 2021)
The development of the era which is increasingly advanced in various field cannot be separated from the development of bank which are not only conventional banks but the emergence of Islamic Bank. Islamic banks exist to meet the needs of society, especially the Muslim community. There are some people who don't even know about the perceptions of Islamic financial institutions. With this research, it is hoped that it will be able to answer problems such as low public knowledge of Islamic financial institutions. The purpose of this research is to determine the public's perception of Islamic financial institutions regarding the interest in using Islamic banks. This type of research uses descriptive qualitative methods by taking 25 informants as samples. The data technique uses observation, interview and documentation methods. The results obtained from this study are people in Adiwerna who already understand Islamic banking but they do not really understand fundraising products even though they have an interest in using Islamic banking.